Geometry‐Mediated Enhancement of Single‐Ion Anisotropy: A Route to Single‐Molecule Magnets with a High Blocking Temperature1. Issue 49 (15th October 2013) - Dey, Mamon; Gogoi, Nayanmoni
<x xml:space="preserve">Abstract</x> Not just any old iron ion: A linear, two‐coordinate ionic FeI complex (see scheme) with a S=3/2 ground state has a large energy barrier for magnetization reversal, Ueff=226 cm−1, and undergoes slow magnetic relaxation in the absence of an applied magnetic field. The preparation of complexes with these properties is a step towards the eventual practical application of single‐molecule magnets.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>